ANALISIS PENCABUTAN HAK MEMANFAATKAN ALAT KOMUNIKASI ELEKTRONIK TERHADAP PELAKU DALAM TINDAK PIDANA INFORMASI DAN TRANSAKSI ELEKTRONIK (STUDI PUTUSAN NOMOR 71/PID.SUS/2023/PN PDL): Analysis of the Revocation of the Right to Use Electronic Communications Against Perpetrators in Information and Electronic Transaction Crimes (Decision Study Number 71/Pid.SuS/2023/PN PDL) - Zalfa Fattaya; Maria Silvya Elisabeth Wangga (AMICUS CURIAE, 2025)
Revenge porn is a type of cyber crime (Cybercrime), the term revenge porn is the act of spreading someone's intimate content without permission, to humiliate or take revenge. The problems in this research are the provisions for revoking the right to use electronic communications for perpetrators of information and electronic transaction crimes in Article 10 of the Criminal Code and Law No. 19 of 2016 and what are the criminal sanctions for perpetrators of information and electronic crimes according to Law No. 1 in 2024 based on study decision number 71/Pid.Sus/2023/PN PDL. The research method used in this thesis is descriptive analytical. Results of research on Case Number 71/Pid.Sus/2023/PN Pdl related to the crime of Information and Electronic Transactions (ITE) which violates Article 27 paragraph (1) in conjunction with Article 45 paragraph (1) of the ITE Law. As well as the panel of judges who impose the main and additional penalties. This research discusses the judge's approach in imposing additional penalties that do not comply with statutory regulations. This decision creates a new legal precedent (judge-made law) by expanding the scope of the Criminal Code in the context of cyber crimes